2021
DOI: 10.3390/ijerph18063201
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Adolescent and Young Couples with Violent Behaviors: Conflict Resolution Strategies

Abstract: Violence in adolescent and young couples is a major issue given its high prevalence and the serious consequences that it brings. For this reason, this research has stated two main objectives. In the first place, to ascertain the level of agreement between both members of the couple both with regard to occurrence and frequency of violence. Second, to ascertain the level of agreement on the frequency of use of conflict resolution strategies in problematic situations in 141 heterosexual couples. The age of the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 60 publications
(75 reference statements)
4
4
0
3
Order By: Relevance
“…Consequently, our first hypothesis is confirmed. In this way, the results are consistent with previous research, which has also highlighted that the aggressions that occur in relationships between young people can be mutual and reciprocal [ 2 , 21 , 22 , 23 , 24 , 25 , 48 , 49 , 50 , 51 ]. Moreover, it is important to highlight that, far from being a phenomenon confined to Latin America, more and more studies reveal similar results in different countries and places around the world [ 13 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consequently, our first hypothesis is confirmed. In this way, the results are consistent with previous research, which has also highlighted that the aggressions that occur in relationships between young people can be mutual and reciprocal [ 2 , 21 , 22 , 23 , 24 , 25 , 48 , 49 , 50 , 51 ]. Moreover, it is important to highlight that, far from being a phenomenon confined to Latin America, more and more studies reveal similar results in different countries and places around the world [ 13 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, we can mention that, although violence in couple relationships can come from any person regardless their sexual orientation, recent studies focused on intimate partner relationships agree that heterosexual couples are characterized by a high prevalence of violence in both men and women [ 49 , 50 , 51 ]. This relational phenomenon could be linked to the normalization of the aggressive patterns of these partners due to an inadequate way of resolving conflicts, a situation that leads to the normalization of violence [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the context of the COVID-19 pandemic, for IPV victims, online help is an important public health service, and the Internet provides more convenient support sources for people seeking help. This study further validates the conclusion of Aguilera-Jiménez et al [ 52 ] by drawing on a larger sample of men. Consequently, this study enriches theories in the field of social help.…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that 42.7% of male victims had suffered from emotional disorders for a long time in the past, and 47.4% of male victims would be willing to seek online help. This verifies that both men and women can be partner abusers [52], and indicates that male IPV victims also have a need to seek help [51]. However, studies assessing the health concerns related to IPV victimization tend to focus on women, rather than men [53].…”
Section: Discussionmentioning
confidence: 93%